Bioactive Metabolites From Acid-Tolerant Fungi in a Thai Mangrove Sediment - Gao, Hai; Wang, Yanan; Luo, Qiao; Yang, Liyuan; He, Xingxing; Wu, Jun; Kachanuban, Konthorn; Wilaipun, Pongthep; Zhu, Weiming; Wang, Yi (Frontiers in Microbiology, 2021)
As a kind of extremophile resources, acid-tolerant fungi and their bioactive metabolites were rarely reported. 237 acidophilic/aciduric fungi were isolated from Thai mangrove sediment in acidic medium (pH 3 and pH 5). With fungal identification technology (morphologic observation, chemical screening, ITS rDNA sequences comparison, etc.), all the isolates were identified and 41 representative ones were selected for analyzing the phylogenetic relationship, which showed 7 genera including Penicillium, Aspergillus, Talaromyces, Cladosporium, Phoma, Alternaria, Trichoderma, in 4 taxonomic orders of phylum Ascomycota, among which Penicillium and Aspergillus were the dominant genera. In the evaluation of acidity tolerance, 95% of the isolates can grow under extremely acidic conditions (pH 2). Among them, 6 strains were assigned as acidophilic fungi that cannot survive under pH 7, of which 83.3% (5/6) have an extraordinarily close genetic relationship belonged to the genus Talaromyces (accounting for half of all the isolated Talaromyces genus), which is the first report on the acidophilic characteristics of this genus. The antimicrobial, anti-tumor and antiviral activities of the fermentation extracts were evaluated. Nearly three-quarters of them (26/41) showed cytotoxic activity, while less than a quarter of them showed antimicrobial (10/41) and anti-H1N1 activities (8/41). The typical aciduric fungus Pencillium oxalicum OUCMDZ-5207 showed similar growth status but completely different chemical diversity at pH 3 and 7. The metabolites of it obtained only under pH 3 were identified as tetrahydroauroglaucin (1), flavoglaucin (2) and auroglaucin (3), among which 3 showed strong selective inhibition on A549 cell with IC50 5.67 μM. These results suggest that acid stress can activate silent gene clusters to expand the diversity of secondary metabolites and bioprospecting on aciduric/acidophilic microorganism resources in Thai mangrove sediment will lead to potential medicinal application.